Diagnostic yield of rapid on-site evaluation transbronchial needle aspiration versus conventional transbronchial needle aspiration: a single center experience - Carmine Guarino; Mariano Mollica; Cristiano Cesaro; Adriano Costigliola; Maria Carolina Micheli; Nadia Corcione; Giuseppe La Cerra; Carmelindo Tranfa; Salvatore Cirillo; Riccardo Smeraglio; Rosario Salvi (Monaldi Archives for Chest Disease, 2020)
Trans-bronchial needle aspiration allows lymph node sampling in several thoracic conditions; the ability of Rapid On-Site Evaluation (ROSE) to predict the final diagnosis in this setting has not been well characterized. We performed a retrospective study to establish the utility of ROSE in the diagnosis of thoracic diseases with mediastinal lymph node involvement. We retrospectively reviewed 297 patients with hilar-mediastinal lymph node enlargement detected at CT scan from January 2013 to April 2016. 201 patients underwent conventional TBNA; in 96 patients, TBNA procedure was performed by on-site presence of a team of pathologists and research morphologists. Lung neoplasms, sarcoidosis, infections and lymphoma were the most common diseases diagnosed with TBNA samples. TBNA simultaneously performed in combination with ROSE produced an increase in percentage of appropriate samples compared to single cTBNA (adequate samples cTBNA vs ROSE-TBNA: 73% vs 81%; p<0.05). Our observations indicate an increase in adequacy of fine needle aspirations and increased diagnostic yield in the ROSE group. In conclusions, ROSE may serve to reduce procedure time and enhance sample triaging therefore limiting the need for further invasive diagnostic testing.